Good Agricultural Practices (GAPs) - Raymond Reyes; Edward Evans (EDIS, 2008)
FE714, a 4-page fact sheet by Raymond Reyes and Edward Evans, provides a brief overview of the concept of GAPs and highlights some of the potential consequences of not instituting GAP guidelines into a farm’s operation. Includes references. Published by the UF Department of Food and Resource Economics, October 2008.